SARS-CoV-2 excretion and genetic evolution in nasopharyngeal and stool samples from primary immunodeficiency and immunocompetent pediatric patients - Haifa Khemiri; Ilhem Ben Fraj; Alessio Lorusso; Najla Mekki; Iolanda Mangone; Mariem Gdoura; Adriano Di Pasqual; Cesare Cammà; Valeria Di Lollo; Asma Cherni; Henda Touzi; Amel Sadraoui; et al. (Virology Journal)
Abstract Background Primary Immunodeficiency disorders (PID) can increase the risk of severe COVID-19 and prolonged infection. This study investigates the duration of SARS-CoV-2 excretion and the genetic evolution of the virus in pediatric PID patients as compared to immunocompetent (IC) patients. Materials and methods A total of 40 nasopharyngeal and 24 stool samples were obtained from five PID and ten IC children. RNA detection was performed using RT-qPCR, and whole-genome sequencing was conducted with the NexSeq 1000 platform. Data analysis used the nextflow/viralrecon pipeline. Hotspot amino acid frequencies were investigated using GraphPad Prism v10. Phylodynamic analysis was conducted with BEAST software. Results In IC children, the viral excretion period lasted up to 14 days in nasopharyngeal swabs, with an average duration of 7 days, and ranged from 7 to 14 days in stool samples. In PID patients, the viral RNA was detected in nasopharyngeal for periods between 7 and 28 days, with an average duration of 15 days, and up to 28 days in stool samples. Two SARS-CoV-2 variants were detected in PID patients: Delta (AY.122) and Omicron (BA.1.1). Patients with antibody and combined deficiencies, exhibited the most prolonged shedding periods in both nasopharyngeal and stool samples and one patient presented complications and fatal outcome. Specific Hotspot amino acid changes were detected in PID: A2821V and R550H (ORF1ab). Conclusion Our findings underscore the prolonged excretion of SARS-CoV-2 RNA in patients with antibody and combined deficiencies. Thus, specialized care is essential for effectively managing PID patients.